PENGARUH PROMOSI GRATIS ONGKIR DAN METODE PEMBAYARAN PAYLATER TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA E-COMMERCE DI INDONESIA (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of free shipping promotions and paylater payment methods on purchasing decisions. The sample in this study were 201 respondents. The sampling method in this study used the cluster random sampling method. The data analysis method used is the Multiple Linear Regression method using the SPSS 26 program. The results of this study indicate that the Free Shipping Promo has a positive and significant effect on purchasing decisions and the Paylater Payment Method has a positive and significant effect on purchasing decisions. In addition, the Free Shipping Promo and the Paylater Payment Method have a simultaneous effect on Purchase Decisions.